2021
DOI: 10.1177/10760296211002900
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Risk Factors of Preoperative Deep Vein Thrombosis (DVT) in Patients With Lower Extremity Fracture

Abstract: Objective: The objective of this work is to discuss and analyze the related factors of lower extremity fracture complicated by preoperative deep vein thrombosis (DVT). Methods: A total of 11,891 patients with closed fractures of lower extremities were selected. By analyzing each patient’s gender, age, presence or absence of diabetes and hypertension, preoperative plasma D-dimer level, and color Doppler ultrasound of the lower extremity vein, the pertinent factors of the patients with lower extremity fractures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Even in studies that confirmed age as an independent risk factor for DVT, there was disagreement about the specific cutoff value for age. Chang et al 15 demonstrated that age above 60 years was an independently associated factor for DVT. Kim et al 16 reported a significant increase in the incidence of DVT in patients with pelvic and acetabular fractures over 50 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Even in studies that confirmed age as an independent risk factor for DVT, there was disagreement about the specific cutoff value for age. Chang et al 15 demonstrated that age above 60 years was an independently associated factor for DVT. Kim et al 16 reported a significant increase in the incidence of DVT in patients with pelvic and acetabular fractures over 50 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Injury site influences the DVT risk for lower limb fractures, even before the added risk of fracture fixation 331 . Around the knee, around the hip, femoral shaft, tibiofibular, and ankle fractures have a DVT prevalence of 8.67%, 6.32%, 5.7%, 2.09%, and 1.97%, respectively 331 .…”
Section: - Do All Orthopaedic Procedures Have the Same Risk Profile F...mentioning
confidence: 99%
“…An example of this is the TKA, a procedure commonly performed on patients with advanced age, obesity, certain degree of post-operative immobilization, and the indication of general anesthesia. Injury site influences the DVT risk for lower limb fractures, even before the added risk of fracture fixation 331 . Around the knee, around the hip, femoral shaft, tibiofibular, and ankle fractures have a DVT prevalence of 8.67%, 6.32%, 5.7%, 2.09%, and 1.97%, respectively 331 .…”
Section: - Do All Orthopaedic Procedures Have the Same Risk Profile F...mentioning
confidence: 99%
“…Injury to the vascular endothelium as a direct result of a fracture can overactivate the clotting system and accelerate thrombosis [ 18 ]. Age, diabetes, and elevated D-dimer levels have been found to be potential risk factors and indicators for preoperative DVT in patients with lower extremity fractures [ 19 ]. Our analysis demonstrated that the incidence of lower limb DVT was higher in patients with medical comorbidities than in patients without medical comorbidities.…”
Section: Discussionmentioning
confidence: 99%